Synthesis and characterization of cross-linked poly (ether sulfone) for a fuel cell membrane - Heo, K.-B.; Lee, H.-J.; Kim, H.-J.; Kim, B.-S.; Lee, S.-Y.; Cho, E.; Oh, I.-H.; Hong, S.-A.; Lim, T.-H. (ELSEVIER SCIENCE BV, 2007)
Cross-linkable sulfonated poly(ether sulfone) copolymer (PES) is synthesized using 4,4'-dihydroxystilbene, hydroquinone 2-potassium sulfonate (HPS) and 4-fluorophenyl sulfone. Cross-linked PES (c-PES) is obtained by UV irradiation of the cross-linkable membrane. The chemical structure and thermal stability of the copolymers are characterized by means of H-1 NMR, FT-IR and TGA techniques. The c-PES 70 membrane, which has 70 mol% of HPS units in the polymer backbone, has a proton conductivity of 0.12 S cm(-1) and good insolubility in boiling water. A catalyst-coated membrane is used to investigate single-cell performance for PEMFC applications. Humidified hydrogen and oxygen are employed as the fuel and oxidant, respectively. A current density of 1500 mA cm(-2) at 0.60 V is obtained at 70 degrees C. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: PROTON-EXCHANGE MEMBRANES; POLY(ETHER SULFONE)S; COPOLYMER MEMBRANES; KETONE); LINKING; ELECTROLYTE; PERFORMANCE